1985
DOI: 10.1159/000124185
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Steroid Regulation of Pulsatile Luteinizing Hormone Release during the Interval between the Mornings of Diestrus 2 and Proestrus in the Rat

Abstract: The object of this study was to determine the influence of ovarian steroids on pulsatile LH release in the interval between the mornings of diestrus 2 (D2) and proestrus in the rat. Four groups of rats were bled continuously for 3 h between 09.30–12.30 h at a rate of 75 µl whole blood/6 min: (1) bled on D2; (2) sham ovariectomy (OVX) on D2 and bled on proestrus; (3) OVX on D2, implanted with empty or oil-filled capsules, and bled 24 h later; and (4) OVX on D2, implanted with estradiol (E2) capsules, and bled 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
20
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 11 publications
8
20
2
Order By: Relevance
“…This finding suggests that estrogen may be responsible for the observed sex-linked differences in susceptibility to cerebral ischemia in experimental stroke. Because OVX rats had decreased plasma levels of gonadal hormones at 24 hours after OVX, 24,25 the different infarct size between the short-term and long-term OVX groups might have resulted from the different durations of gonadal hormone depletion. The effects of estrogen on regional CBF reductions during ischemia remain controversial in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests that estrogen may be responsible for the observed sex-linked differences in susceptibility to cerebral ischemia in experimental stroke. Because OVX rats had decreased plasma levels of gonadal hormones at 24 hours after OVX, 24,25 the different infarct size between the short-term and long-term OVX groups might have resulted from the different durations of gonadal hormone depletion. The effects of estrogen on regional CBF reductions during ischemia remain controversial in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Both physiological high and physiological low doses (10 and 60 pg/mL of plasma estradiol concentration, respectively) were equally effective at reducing the size of ischemic injury. 8 Therefore, the relatively lower dose of estradiol valerate used in the present study was considered to be adequate to analyze the neuroprotective role of estrogen against brain ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that mean blood LH levels rapidly increased Received: April 15. 1985 Accepted after revision: October 7, 1985 within 24 h following ovariectomy (OVX) on diestrus I (Dl) and diestrus 2 (D2) due to increases in both LH pulse amplitude and frequency, suggesting an inhibitory role for ovarian steroids on these parameters of LH secretion in the intact rat [27,28], Results of studies in which physiological levels of estradiol (E2) and/or progesterone (P) were re …”
mentioning
confidence: 99%
“…This may explain why elevated levels of progesterone oc curring during diestrus I and diestrus 2 do not block pulsatile LH secretion. There is ample evidence that estradiol can act during the estrous cycle to restrain GnRH and hence LH secre tion [26,27]. Using a different protocol (rats OVX on the mor ning of proestrus and receiving various steroid regimens during proestrus), Leipheimer et al [27] concluded that estradiol secre tion during proestrus was primarily responsible for restraining LH pulse frequency on estrus, while estradiol and progesterone acted together to suppress pulse amplitude.…”
Section: Discussionmentioning
confidence: 99%